2020
DOI: 10.1136/thoraxjnl-2019-214168
|View full text |Cite
|
Sign up to set email alerts
|

Sputum microbiome profiling in COPD: beyond singular pathogen detection

Abstract: Culture-independent microbial sequencing techniques have revealed that the respiratory tract harbours a complex microbiome not detectable by conventional culturing methods. The contribution of the microbiome to chronic obstructive pulmonary disease (COPD) pathobiology and the potential for microbiome-based clinical biomarkers in COPD are still in the early phases of investigation. Sputum is an easily obtainable sample and has provided a wealth of information on COPD pathobiology, and thus has been a preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 89 publications
(131 reference statements)
0
44
0
Order By: Relevance
“…and respiratory virus infection (40), and our study failed to analyze the effect of glucocorticoids on virus infection. Finally, the bronchoalveolar lavage fluid (BALF) microbiology has great significance when studying the lung microbiome (12,41), and further investigation of the microbiome via analysis of AECOPD patients' BALF is needed.…”
Section: Discussionmentioning
confidence: 99%
“…and respiratory virus infection (40), and our study failed to analyze the effect of glucocorticoids on virus infection. Finally, the bronchoalveolar lavage fluid (BALF) microbiology has great significance when studying the lung microbiome (12,41), and further investigation of the microbiome via analysis of AECOPD patients' BALF is needed.…”
Section: Discussionmentioning
confidence: 99%
“…metagenomics data suggesting their diverse role in the pathophysiology of human diseases (Man et al, 2017;Ditz et al, 2020;Khatiwada and Subedi, 2020). However, the mechanisms for the pathophysiology of COVID-19 and other respiratory tract diseases (non-COVID) as well as specific host-microbiome interactions supporting the changes in microbiome compositions, are considered below and not well-established.…”
Section: Discussionmentioning
confidence: 99%
“…however, further analysis found that these samples are very similar in terms of the abundance of oral ora [24]. Therefore, we believe that although there are differences in microbial composition between samples from the upper respiratory tract and the lower respiratory tract, sputum does re ect the microbial composition of the lower respiratory tract to some extent, especially in terms of abundance [25].…”
Section: Discussionmentioning
confidence: 94%